Gamma-Ray Emission from Be/X-Ray Binaries - Orellana, Mariana Dominga (2005)
Be/X-ray binaries are systems formed by a massive Be star and a magnetized neutron star, usually in an eccentric orbit. The Be star has strong equatorial winds occasionally forming a circumstellar disk. When the neutron star intersects the disk the accretion rate dramatically increases and a transient accretion disk can be formed around the compact object. This disk can last longer than a single orbit in the case of major outbursts. If the disk rotates faster than the neutron star, the Cheng-Ruderman mechanism can produce a current of relativistic protons that would impact onto the disk surface, producing gamma-rays from neutral pion decays and initiating electromagnetic cascades inside the disk. In this paper we present calculations of the evolution of the disk parameters during both major and minor X-ray events, and we discuss the generation of gamma-ray emission at different energies within a variety of models that include both screened and unscreened disks.